Expanding on Wabi-Sabi as a philosophy in college students during the Covid-19 pandemic - Chittajallu, Lohith; Ryška, Tomáš, 1976-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
Students Mental health and academic performance in the education industry has always been of high regard. The Covid-19 Pandemic has led to discrepancies and increasing concern over these issues. This research aims is to understand and assess various themes related to mental health and academic performance among college students and analyze whether inculcating Wabi-Sabi into day-to-day life during this pandemic crisis can positively impact students. The research is based on qualitative and ethnographic methods; where all the findings are based on ethnographic evidence observed during the fieldwork. The paper runs through a literature review, followed by ethnographical and on-site personal communication with the participants explaining their perspectives and combining them to analyze the effect of Wabi-Sabi on them during the pandemic. The results were theoretical analysis on how participants showed a positive impact on mental health and increased academic performance despite the hassles that were caused due to the Covid-19 pandemic.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses